VOICES FROM THE CLASSROOM: INTEGRATING 21ST CENTURY SKILLS IN TURKISH PRIVATE SCHOOL EFL EDUCATION – A QUALITATIVE PERSPECTIVE - Akyıldız, Seçil Tümen; Şahin, Fatmanur (Ümit YILDIZ, 2024)
This qualitative study explores the integration of 21st-century skills in English as a Foreign Language (EFL) education within Turkish private schools. Focusing on the 4Cs—communication, collaboration, critical thinking, and creativity—the research examines how nine EFL teachers in Malatya incorporate these competencies into their teaching practices. The study employs semi-structured interviews to gain insights into teachers' methods, challenges, and perceptions regarding the use of technology, fostering critical thinking and problem-solving skills, enhancing communication and collaboration, and encouraging creativity and innovation. Findings reveal that teachers effectively use tools such as interactive whiteboards, digital platforms, and project-based learning to create dynamic and engaging lessons. They also employ techniques like Socratic questioning, debates, and role-playing to develop students' cognitive and linguistic abilities. Despite the benefits, challenges such as technological proficiency and equitable access to resources persist. The study underscores the importance of continuous professional development and support for teachers to optimize the integration of 21st-century skills in EFL education. Future research should explore long-term impacts and additional methods to support innovative teaching practices. This study contributes to the advancement of EFL education in Turkey and offers valuable insights for educators globally, highlighting the need for holistic development to prepare students for modern life and work environments.

This qualitative study explores the integration of 21st-century skills in English as a Foreign Language (EFL) education within Turkish private schools. Focusing on the 4Cs—communication, collaboration, critical thinking, and creativity—the research examines how nine EFL teachers in Malatya incorporate these competencies into their teaching practices. The study employs semi-structured interviews to gain insights into teachers' methods, challenges, and perceptions regarding the use of technology, fostering critical thinking and problem-solving skills, enhancing communication and collaboration, and encouraging creativity and innovation. Findings reveal that teachers effectively use tools such as interactive whiteboards, digital platforms, and project-based learning to create dynamic and engaging lessons. They also employ techniques like Socratic questioning, debates, and role-playing to develop students' cognitive and linguistic abilities. Despite the benefits, challenges such as technological proficiency and equitable access to resources persist. The study underscores the importance of continuous professional development and support for teachers to optimize the integration of 21st-century skills in EFL education. Future research should explore long-term impacts and additional methods to support innovative teaching practices. This study contributes to the advancement of EFL education in Turkey and offers valuable insights for educators globally, highlighting the need for holistic development to prepare students for modern life and work environments.
VOICES FROM THE CLASSROOM: INTEGRATING 21ST CENTURY SKILLS IN TURKISH PRIVATE SCHOOL EFL EDUCATION – A QUALITATIVE PERSPECTIVE
Keywords: English As A Second Language; İkinci Bir Dil Olarak İngilizce